Effectiveness of 8 weeks of vestibular exercises on stress, sleep, and cognitive parameters in hypertensive patients - Yuvaraj Subramani Sagadevan; Shyma Parapurath; Anurag Kesarwani; Goothy, Sai Sailesh kumar; Anita Choudhary; Rohit Singh Chouhan; Potey Gajanan Govind; Prateek Prabhaker Awasthi (Asian Journal of Medical Sciences, 2022)
Background: It was hypothesized that vestibular stimulation causes beneficial effects in hypertensive patients as so as in diabetic individuals. Aims and Objectives: The present study was undertaken to observe the effectiveness of 8 weeks of vestibular exercises on stress, sleep, and cognitive parameters in hypertensive patients. Materials and Methods: A total of eighty male and female stage 1 hypertensive individuals were part of the study after obtaining voluntary, written informed consent. Vestibular exercises comprising three steps with a time period of 45 min per session were administered to the participants of the intervention group. Two sessions per week were administered as mentioned in the literature. Stress levels were assessed by the perceived stress scale. Sleep was assessed by the insomnia severity index. A spatial and verbal memory test was used to assess the spatial and verbal memory scores. Results: There was no significant difference in the demographical parameters of the control and intervention groups. There is no significant difference in stress, sleep scores, and spatial and verbal memory scores among the control and intervention groups. There was a significant decrease in the stress scores and insomnia scores, and a significant improvement in the spatial and verbal memory scores in the intervention group after the intervention when compared with the control group. Conclusion: The present study results suggest that vestibular exercises have a positive impact on reducing stress and improving sleep and cognition in hypertensive individuals. The study highlights the need for further detailed studies in this area to recommend the inclusion of vestibular exercises as adjunctive therapy in the management of hypertension.